The exposure to biologic and targeted synthetic disease-modifying antirheumatic drugs in pregnancy and lactation - Góralczyk, Alicja; Kolossa, Katarzyna; Waszczak-Jeka, Marzena; Adamczak, Rafał; Jeka, Sławomir (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Chronic inflammatory diseases often affect women of childbearing age. Since biologic and targeted synthetic disease-modifying antirheumatic drugs (bDMARDs and tsDMARDs) are more available, their use during conception, pregnancy and lactation has become a matter of concern. Current studies prove the safety of innovative therapy in pregnant women and may contribute to its wider use than before in pregnancy and lactation. It mainly concerns tumour necrosis factor a (TNF-a) inhibitors. We searched PubMed using Medical Subject Headings (MeSH) terms and identified relevant studies and guidelines. We present up-to-date knowledge of bDMARDs and tsDMARDs safety in pregnant and breastfeeding women.